TAp73 promotes anti-senescence-anabolism not proliferation - Agostini, Massimiliano (Impact Journals LLC, 2014)
TAp73, a member of the p53 family, has been traditionally considered a tumor suppressor gene, but a recent report has claimed that it can promote cellular proliferation. This assumption is based on biochemical evidence of activation of anabolic metabolism, with enhanced pentose phosphate shunt (PPP) and nucleotide biosynthesis. Here, while we confirm that TAp73 expression enhances anabolism, we also substantiate its role in inhibiting proliferation and promoting cell death. Hence, we would like to propose an alternative interpretation of the accumulating data linking p73 to cellular metabolism: we suggest that TAp73 promotes anabolism to counteract cellular senescence rather than to support proliferation.